Preservation by ‘Letting Go’: Buddhist Impermanence (Anicca) in Ruether’s Ecotheology - Ahern, Annette (Journal for the Study of Religion, Nature and Culture, 2006)
Christianity, Judaism and Buddhism contain rich teaching and motivational resources that pertain directly to the struggle for environmental justice in this age of what Engaged Buddhist leader Sulak Sivaraksa identifies as global militaristic capitalism. Guided by the work of ecofeminist theologian Rosemary Ruether and Buddhist scholar Rita Gross, this paper explores meanings and symbols within Judaism, Christianity, and Buddhism that promote environmental values and practice. The paper begins with an overview of Ruether’s interpretation of the covenantal and sacramental traditions in Judaism and Christianity (1992 and 2000) followed by a close look at the dialogue between Gross and Ruether (2001) in which the relevance of the Buddhist teachings concerning impermanence (anicca) and interdependence for the environmental movement is unfolded. This article concludes by articulating a different interpretive strategy for accessing the Christian community than that provided by Ruether while at the same time building on her work.